Improving Vocabulary Using a Computer-based Flashcard Program - H Hasbullah; Sanitah Bte Mohd Yusof; Muhammad Yaumi; Adamu Mallam Babikkoi (International Journal on Advanced Science, Education, and Religion, 2018)
Numerous complications in conveying students’ideas and comprehending the words from teachers due to lack of academic vocabulary Many teaching techniques or strategies the teacher can use to make students learn the vocabulary effectively. This study aims at examining the effectiveness of Computer-based Flashcard Program (CFP) is effective in teaching vocabulary. Pre-experimental method with one group pretest and posttest was the design of this study. This study involved thirty one students of Islamic Junior High School in Makassar city, Indonesia chosen conveniently. The data were collected through a vocabulary test to examine the effectiveness of CFP to improve the vocabulary mastery using t-test. The result of the data analysis showed that there was a significant difference between pretest and posttest. This study found that use of CFP is effective to improve vocabulary mastery